Anti-Tumor Effect of Non-Thermal Atmospheric Pressure Plasma-Activated Medium on Synovial Sarcoma: An In Vitro and In Vivo Study - Hana Yao; Hiromitsu Toyoda; Naoki Takada; Naoto Oebisu; Kumi Orita; Yoshitaka Ban; Kosuke Saito; Katsumasa Nakazawa; Yuto Kobayashi; Hiroshi Taniwaki; Chinatsu Ohira; Jun-Seok Oh; et al. (Biomedicines)
Background/Objective: Anti-tumor effects of plasma-activated medium (PAM) were demonstrated using various malignant tumors. However, the anti-tumor effect of PAM on synovial sarcoma remains unclear. Therefore, we aimed to investigate the anti-tumor effects of PAM on synovial sarcoma and its underlying mechanisms, focusing on the quantitative analyses of both intracellular reactive oxygen species (ROS) and cell apoptosis. Methods: The human synovial sarcoma cell line HS-SY-II was used to investigate the cell viability after PAM treatment. We investigated the anti-tumor effects and side effects of local PAM injection in a synovial sarcoma xenograft murine model. Moreover, we observed PAM-induced intracellular ROS accumulation and cell apoptosis and assessed the involvement of intracellular ROS in the anti-tumor effects of PAM using an intracellular ROS scavenger. Results: PAM significantly decreased the viability of synovial sarcoma cells compared with untreated Dulbecco’s modified Eagle medium. Local PAM injection into a synovial sarcoma xenograft murine model significantly suppressed tumor growth, including tumor volume (p < 0.001) and weight (p = 0.031), without side effects. Regarding anti-tumor mechanisms, PAM induced significant cell apoptosis and intracellular ROS accumulation (p < 0.001). The intracellular ROS scavenger significantly inhibited the anti-tumor effect of PAM (p < 0.001). Conclusions: We confirmed the anti-tumor effects of PAM on synovial sarcoma in vitro and in vivo, as well as the absence of side effects. The underlying mechanism was suggested to involve cell apoptosis induced by intracellular ROS accumulation. Considering the various clinical issues associated with the existing treatments of synovial sarcoma, PAM is a promising new option.